1984
DOI: 10.1159/000260786
|View full text |Cite
|
Sign up to set email alerts
|

Migration of Fluoride in the Mouth

Abstract: This paper describes an attempt to follow the migration of fluoride in the mouth following dissolution of a fluoride tablet, placed at one asymetrically situated position in the mouth, by measuring fluoride concentrations in saliva and by using particles of dentine as semi-quantitative fluoride monitors. The findings demonstrate the failure for the fluoride released from the tablet to result in an overall, elevation of fluoride levels in the oral environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 7 publications
4
23
0
Order By: Relevance
“…in the present study was qualitatively similar to that previously de scribed for fluoride [Weatherell et al, 1984. Concentrations at specific sites were very different from those in samples of 'whole' saliva, sometimes greater, often smaller.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…in the present study was qualitatively similar to that previously de scribed for fluoride [Weatherell et al, 1984. Concentrations at specific sites were very different from those in samples of 'whole' saliva, sometimes greater, often smaller.…”
Section: Discussionsupporting
confidence: 88%
“…Meyer [1969], Weatherell et al [1984] and Primosch et al [1986] have demonstrated this using fluo ride and Jenkins and Krebsbach [1985] described a similar situation in the case of particulate charcoal. Rates of clearance also vary considerably from site to site Britse and Lagerlof, 1987], The combination of these two factors has a marked effect on the way the mouth handles soluble materials.…”
mentioning
confidence: 86%
“…1 In newly erupted teeth, the enamel is porous; thus, it dissolves more easily in comparison with adult enamel. 5 A drop in the pH of dental plaque occurs after consuming carbonated drinks, which takes 20 to 30 minutes to get neutralized by saliva. Although a few attacks may not be harmful, a frequent consumption may lead to deleterious effect.…”
Section: 5005/jp-journals-10024-2166mentioning
confidence: 99%
“…The simulations in figures 4 and 5 indicate just how much the positiondependent contact which has been shown to exist be tween the plaque surface and the saliva [Weatherell et al, 1984[Weatherell et al, , 1986Lecomte and Dawes, 1987] will affect the course of a Stephan curve and the resultant de mineralisation. Lingual intra-oral sites correspond to values of FILMTIME in the range 0-0.5 min, while those for buccal sites, depending on location, corre spond to values in the range 2-4 min.…”
Section: Simulation O F the Caries Processmentioning
confidence: 99%
“…Weatherell et al [1984Weatherell et al [ ,1986 placed tab lets at different sites in the mouth, while Lecomte and Dawes [1987] fixed a small gel-containing reservoir to the teeth at various sites. The rates of dissolution of the tablet, or clearance of solute from the gel, were then used as indicators of the rate of exchange be tween the plaque surface at this site and the bulk sa liva.…”
mentioning
confidence: 99%